Disjuntivas do proceso de cambio: o avanço das classes subalternas, as contradições do estado plurinacional da Bolívia e o horizonte do socialismo comunitário - Valença, Daniel Araújo (2017)
This thesis aims to analyze the political, economic, cultural and legal process experienced by Bolivia in the late decades, over a thorough totality and historicaldialectical perspective. For such, I have implemented extensive research on documents and bibliographies, along the scopes of History, Law, Economics and Political Science, in order to look upon and study the Bolivian social formation. I have also conducted open interviews with leaders of Estado Plurinacional (Bolivian Republic), social and intellectual movements, to make a standpoint besides the documents and literature canon. Moreover, even with no purpose of making ethnography, I have lived during four months some experiences and have faced the realities of this Andean country, from which I could realize another way of looking through the extensive bibliography related to Bolivia in the current 21st century. The analysis was prior and later conceived from historical-dialectical materialism lenses and theoretical matrices based on Marxist sources. Thus, to achieve such an object, this thesis is structurally presented as follows: first, I recover the history of Marxism in Latin America, as well as I set the lines of the main categories that support this thesis, especially the historicity, the dialectics and the totality. After that, I look at the Bolivian social formation, which is rooted in the Inca Empire and colonial society and, because of that, ends up showing a particular interweaving between class and ethnicity. It is from this formation that becomes possible to understand the state crisis occurred under the republican time and the popular uprisings in this early 21st century. The latters, immediately originated from the depreciation of social reproduction conditions due to the apparatus of dispossessional acumulation, represented the encounter – into history – of the several struggles of low-class groups, such as, for instance, indigenous uprisings in the 18th and 19th centuries and further with the workers and peasants in the 20th century. It is the indigenous peasantry that transforms economical-corporate demands into ethical-political actions and represents the popular claims for an autonomous political project of lowclass groups. At the front of a government project, the peasant-indigenous-popular union imposed changes in the national economic logics simultaneously spreading new force-ideas of a state institutionality, accomplished in the State Political Constitution of 2009. The legal canon, in general, only emphasizes the influence of the indigenous cosmovisions on its typologies and concepts. An analysis of the Bolivian social formation, of the ongoing political process and of the constitutional arrangements, however, reveals the inter-purtenance of national-popular and indigenous-communitary horizons, with prominent arise of the former, because of the specific profile of the individual who leads the so-called “Proceso de Cambio” (Changing Process). The Plurinational State of Bolivia has its foundations in the shift of power correlations between the Bolivian social classes and, as such, constitutes a form of state in transition either to the strengthening of Proceso de Cambio towards “Communitary Socialism” or to a conservative turn.